Healthcare Access Inequities Experienced by Patients Supported by Cancer Patient Navigators (NAPAK) - Jelita Jelita; Allenidekania Allenidekania; Tuti Nuraini; Riri Maria; Ucip Sucipto (FORIKES, 2026)
Cancer patients in Indonesia continue to experience substantial inequalities in accessing healthcare services, driven by structural, geographical, financial, and informational barriers. These disparities often result in delayed diagnosis, fragmented care, and adverse health outcomes. This study aimed to explore the lived experiences of cancer patients receiving navigation services from Cancer Patient Navigators (NAPAK) and to examine how these experiences reflect broader patterns of healthcare access inequality. A qualitative descriptive phenomenological design was employed, involving ten purposively selected participants who met the inclusion criteria. Data were collected through in‑depth interviews and analyzed using thematic analysis supported by NVivo 14 software. Four major themes emerged from the analysis: (1) various healthcare access inequalities, including saturated schedules, complex administrative procedures, geographical distance, financial constraints, and appointment difficulties; (2) the primary role of cancer patient navigators, who provided essential informational, procedural, emotional, and advocacy support throughout the care continuum; (3) transportation and access disparities, highlighting both accessible and severely limited mobility conditions across regions; and (4) the impact of healthcare access disparities on health, reflected in heightened anxiety, psychological distress, physical exhaustion, and emotional burden. Participants also expressed expectations for improved navigation services, enhanced facilities, clearer information systems, and stronger governmental support for insurance programs. The study concludes that healthcare access inequality significantly shapes cancer patients’ physical and psychological well‑being. Strengthening communication between healthcare providers and patients, improving navigation services, and enhancing policy support are critical to reducing disparities and promoting equitable cancer care.Keywords: cancer patient navigation; healthcare access inequality; transportation barriers; patient experience